2022
DOI: 10.3329/jbcbm.v7i2.60146
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Yield Performance of Green Capsicum (Capsicum Annuum L.) As Influenced by Vermicompost Application Grown at Rooftop Of Chandpur Area

Abstract: A pot experiment was conducted during rabi season during 2020-21 at a rooftop of Chandpur 150 MW Combined Cycle Power Plant (CCPP) Area in Chandpur Sadar upazila under Chandpur district to study the impact of different dosages of vermicompost (VC) on the growth and yield parameters of green capsicum plants (Capsicum annuum L.). It was laid out in a randomized complete block design (RCBD) with three replications each of six treatments viz. T1: 0 ton VC ha-1 (control), T2: 2.5 ton VC ha-1, T3: 5 ton VC ha-1, T4:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This showed that over-treatment of chemical fertilizer causes problems not only to the soil health but also to the human health and physical environment (12,13) . Organic farming for capsicum production is increasing day by day in Bangladesh (14) .…”
Section: Introductionmentioning
confidence: 99%
“…This showed that over-treatment of chemical fertilizer causes problems not only to the soil health but also to the human health and physical environment (12,13) . Organic farming for capsicum production is increasing day by day in Bangladesh (14) .…”
Section: Introductionmentioning
confidence: 99%
“…(15) when growing eggplant using Vermicompost fertilizer compared to chemical fertilization and the measurement treatment, the organic fertilizer treatment has a significant effect on plant growth and production cost. (19) indicated that adding earthworm fertilizer at different levels has a significant effect on the growth, yield and quality of pepper.…”
Section: Introductionmentioning
confidence: 99%